The Effect of Practice and Visual Feedback on Oral-Diadochokinetic Rates for Younger and Older Adults. (March 2018) - Ben-David, Boaz M.; Icht, Michal
Assessments of oral-diadochokinetic rates are commonly performed to evaluate oral-motor skills. However, the appropriate administration protocol is not defined, and varies across therapists, clinics and laboratories. In three experiments and an auxiliary one, this study analyzes the effects of brief (motor) practice and visual feedback on the performance of 98 younger (20–40 years old) and 78 older adults (over 65) with the sequential motion rate (SMR) version. Overall rates were significantly faster for younger over older adults. Irrespective of age-group, averaged performance was significantly better on the second round, but the third round was found to be superfluous, across experiments and age-groups. Visual feedback (using a mirror) was found to be detrimental for younger adults, eliminating the advantage reaped from a practice round. For older adults, visual feedback did not alter the effect of a practice round. Sensory (visual) degradation is presented as a possible source for this age-related difference. We discuss these findings and suggest an administration protocol for younger and older adults with the SMR version, including a total of two rounds and no visual feedback.